POWER OF WOMAN: GLENN CLOSE’S HEROINES AS THE EMBODIMENT OF STRONG FEMALE CHARACTERS IN CINEMA (SOCIOLOGICAL ANALYSIS) - Anna A. Podolskaya (Russian Studies in Culture and Society)
The article is devoted to the sociological analysis of films featuring Hollywood actress Glenn Close. The purpose of the research is to analyze in what image the heroines appear, how their characters relate to the time of action in films.